Clinical researchs and advances of risk factors for major cardiovascular adverse events in patients with chronic kidney diseases - Li Jin-long; Hu Yu-gang; Zhou Qing (Linchuang shenzangbing zazhi)
Chronic kidney disease (CKD) patients have a variety of systemic complications and multiple organ dysfunctions due to the injuries of renal structures and functions, compromising quality-of-life and seriously threatening patient well-being. Among these CKDs, major cardiovascular adverse events (MACE) lead to adverse outcomes. However, risk factors of MACE in general population have certain limitations in guiding clinical treatments and risk evaluations of CKD patients. With recent medical advances, identifying and evaluating risk factors for MACE have made great strides in CKD patients and a large variety of clinical indicators and parameters have been adopted for researches. Here current understanding of risk factors of MACE of CKD patients was summarized to provide references for clinical practices.